Overcrowded Schools and Quality of Teaching in Goma’s Public Secondary Schools - Master Matabaro Simweray Isabelle (IJRDO- Journal of Educational Research, 2024)
This research, entitled "Overcrowded Class Sizes and Quality of Teaching in Goma’s Public Secondary Schools," aims to highlight the influence of overcrowded classrooms on the quality of teaching in public secondary schools in the city of Goma, Democratic Republic of Congo. To conduct this study, we used simple random sampling of teachers, relying on their pedagogical training and their ability to assess the didactic implications of learning in an overcrowded environment. To this end, we adopted qualitative and quantitative methods, as well as supporting techniques such as anthropological-dialectical analysis, indirect observation, analytical methods, interviews, and documentary research. To achieve the objective of this research, we targeted 15 schools, where we took a total sample of 300 students, 80 teachers, and 20 administrative staff. According to teachers and administrators,the quality of teaching is poor due to the detrimental consequences of overcrowded classrooms, including poor teaching quality resulting from demotivation due to low wages, and the difficulty of monitoring and supervising students